2008
DOI: 10.1088/0953-8984/20/24/245101
|View full text |Cite
|
Sign up to set email alerts
|

Long-term physical ageing in As–Se glasses with short chalcogen chains

Abstract: Long-term physical ageing of chalcogenide glasses, which occurs over tens of years, is much less understood than the short-term ageing. With Se-rich underconstrained As 30 Se 70 glass as a model composition (consisting of Se n chains with n 3 on average), a microscopic model is developed for this phenomenon by combining information from differential scanning calorimetry, extended x-ray absorption fine structure, Raman, and 77 Se solid state nuclear magnetic resonance spectroscopies. The accompanying changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
33
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 35 publications
0
33
0
Order By: Relevance
“…ageing has been investigated in these chalcogenide networks [513,514,515]. Also, since the enthalpic loss is directly related to T g − T w , ageing is enhanced for compositions which have a lower T g (i.e.…”
Section: Chalcogenidesmentioning
confidence: 99%
See 1 more Smart Citation
“…ageing has been investigated in these chalcogenide networks [513,514,515]. Also, since the enthalpic loss is directly related to T g − T w , ageing is enhanced for compositions which have a lower T g (i.e.…”
Section: Chalcogenidesmentioning
confidence: 99%
“…When two types of glasses are compared (20 years aged and rejuvenated), Raman spectroscopy of As-Se [513] seem to indicate small changes changes in bond statistics (as for NMR), and for Se-rich glasses, it was concluded that Se ring-like structure collapse and lead to a reorganization of chain fragments between AsSe 3/2 units. On the overall, these different probes signal that As-Se-Se-As motifs convert into As-SeAs and As-Se-Se-Se-As fragments during ageing.…”
Section: Chalcogenidesmentioning
confidence: 99%
“…Thus, PAL investigations of ageing phenomena in metallic light alloys and organic polymers [6][7][8][9][10][11][12][13] allowed significant progress in the models of natural structural relaxation in these materials [6][7][8][9][10][11][12][13]. At the same time, the mechanisms of PhA in network glasses (oxide and chacogenide, in part) are proposed at the basis of results obtained by various structure-sensitive probes solely [14][15][16][17], while complementary part of information on void-species behaviour is missing. This obstacle hinders the development of unified model for structural relaxation in chalcogenide glasses (ChG), having impact also on our understanding of PhA in disordered materials with more complicated structures.…”
mentioning
confidence: 99%
“…Strong endothermic peak superimposed on the endothermic step of the glass transition signal and a displacement towards higher/lower temperature of T g usually appear as a result of prolonged storage/ annealing [19,20,23], photoexposure [24] or maintenance in stationary high-energy radiation fields [25]. Along with the enthalpy losses (DH), which are usually used to describe PhA kinetics [19,20,[23][24][25], the changes in the onset value of T g and partial area A, as determined from DSC heating curves, could be also used as suitable parameters for characterization of PhA effect in ChG [14,15,18]. Frankly speaking, T g value as determined from DSC heating curves depends significantly on the cooling rate through the glass transition region, used during synthesis [26,27].…”
mentioning
confidence: 99%
See 1 more Smart Citation